Nutritional knowledge of mothers, children’s food consumption, and stunting prevalence: a study of indigenous community in Kasepuhan of Ciptagelar and Sinar Resmi, West Java, Indonesia - Patriasih, Rita; Khomsan, Ali; Hadi Riyadi; Widiaty, Isma; Anwar, Faisal; Wigna, Winati; Firdausi, Alya (International Journal Of Community Medicine And Public Health, 2023)
Background: The indigenous community of Kasepuhan of Ciptagelar lives in villages that still hold the local traditions firmly. In contrast, the indigenous community of Kasepuhan of Sinar Resmi geographically live in more open villages, so they can easily interact with people from other villages. Culture contributes social values to food consumption and nutritional status. Methods: This cross-sectional study was conducted on the two indigenous communities from January 2015 until June 2016. The study involved selecting samples using stratified random sampling. The total sample was as many as 200 households. Results: The study found that 70.3% of mothers in Kasepuhan of Ciptagelar and 48.6% in Kasepuhan of Sinar Resmi have low nutritional knowledge (score <60). The households living in both Kasepuhans had high dietary consumption diversity. However, a household in Ciptagelar had a higher dietary diversity score (6.4±1.4) than in Sinar Resmi (5.7±2.0) (p=0.032). The foods taboo for pregnant mothers were meatballs, Reundeu leaves, durian, pineapple, and Ambon banana. The foods taboo for children under five were meat, chicken feet, chicken tail, chicken liver, chicken gizzard, and seafish. The stunting prevalence of children in Ciptagelar was 44.3%, while Sukaresmi was 22.9%. Conclusions: Based on those findings, the mother’s nutritional knowledge in Kasepuhan of Sinar Resmi was better than in Kasepuhan of Ciptagelar. The diversity of household food consumption in Kasepuhan of Ciptagelar was higher. However, there was a possibility that the nutritional intake of children in Kasepuhan of Ciptagelar was lower. Consequently, the stunting prevalence was higher in Kasepuhan of Ciptagelar than in the Kasepuhan of Sinar Resmi.